The Sensibility of the Subject as a Condition of Its Freedom: A Counterpoint Between Kant and Schiller - Fragomeno González, Darío (2025)
The philosophy of German idealism is influenced by the French Revolution, not only in its political dimension but also in the epistemological one. This article addresses the latter aspect, focusing on Friedrich Schiller´s aesthetics, highlighting how it becomes the former, as they are dialectically related. Consequently, the debate centers on how aesthetics constitutes an enlightened subjectivity. Schillerian subjectivity is studied through the role of autonomy, as it is fundamental to human freedom. Such a role implies a moral imperative, that is, an ethics aligns with the Enlightenment process marking the transition from the Medieval to the Moden era. Therefore, education becomes a central element in civic formation, based on Enlightenment aesthetics.